Quiet Quitting Behavior as an Impact of Psychological Distress: Well-being, Anxiety, and Depression as Mediating Variables - Rahwana Mustafa; Majang Palupi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine quiet quitting behavior as an impact of psychological distress with well-being, anxiety, and depression as mediating variables in employees at PT Jamkrindo Solo. The sampling technique in this study is a census technique that uses the population in the research area as a sample. The questionnaire was distributed directly to 33 employees. The research model was analyzed using SEM-PLS. The results of the data analysis show that psychological stress has a negative and insignificant effect on the desire to quiet quitting. In addition, psychological distress directly showed a significant and positive influence on well-being, anxiety, and depression. However, well-being, anxiety, and depression directly have no substantial and negative effect on quiet quitting cessation. Psychological distress indirectly had a positive influence on quiet quitting cessation through the mediation of well-being. Psychological distress indirectly has a negative and insignificant impact on quiet quitting through the mediating variables of anxiety and depression in employees at PT Jamkrindo Solo.